Coatings and Films - Muthusamy, Ramya; Sengodan, Thangaprakash; Andronov, Volodymyr; Otrosh, Yurii; El Moussaouy, Abdelaaziz (Trans Tech Publications Ltd, 2023)
This special publication presents to readers the latest engineering investigations in the area of materials science including thin films and nanomaterials for microelectronics and surface treatment technologies in machinery. The special edition will be useful to many researchers and engineers whose activities are related to machinery and electronics. Coating, Surface Treatment, Grinding, Cold Spraying, Laser Hardening, Thin Films, Spray Pyrolysis, Chemical Bath Deposition, Optical Properties, Gallium Arsenide, Quantum Dots, Quantum Wells, Low Dimensional Quantum Structure Materials Science, Nanoscience.
Keywords: Coatings.; Thin films.; elektronické knihy; electronic books